Asking the Menstruation Question to Achieve Menstrual Justice - Johnson, Margaret E. (Columbia Journal of Gender and Law, 2021)
Menstruation is a situs of discrimination, oppression, harassment, and microaggression. Employers fire workers for bleeding and experiencing period pain. Schools control menstruating students’ access to bathrooms, products, and menstrual education. Prisons control their residents’ free access to menstrual products. There are both “obvious and non-obvious relationships” between menstrual discrimination and discrimination on the basis of race, gender, class, gender identity, and disability. This Essay suggests we ask the “menstruation question” as part of our examination of all forms of intersectional oppressions and to achieve menstrual justice. For example, if we see something racist, we should ask “where is the menstrual oppression in this?” So too, if we see menstrual oppression, we should ask, “where is the racism in this?” Through this process, we discover the multidimensionality of menstrual injustices and how they operate as structural intersectionality. We learn that “dismantling any one form of subordination is impossible without dismantling every other.” Therefore, asking the menstruation question is critical to achieve menstrual justice.